(untitled) (Rev. iberoam. bioecon. cambio clim., 2022)
In Latin America, Chagas disease is a significant public health threat and canines play an important role in the domestic transmission cycles of Trypanosoma cruzi. This report presents a case of Chagas in a two-month-old male mongrel dog that was rescued and taken to the private Royal Pets Veterinary Clinic in the City of Managua - Nicaragua. The animal was in a cachectic state, weak and completely wet, presenting a rectal temperature of 33.6 ° C, dehydration (9%), pale mucous membranes, non-reactive lymph nodes, distended abdomen without pain on palpation, bloody ulcerative lesion in the left rib cage. In peripheral smear examination, the blood parasite Trypanosoma was detected; in addition, in the PCR analysis, amplification was obtained for Trypanosoma cruzi, but negative for Trypanosoma vivax and Trypanosoma evansi. The detection and identification of this case could raise awareness in the country about the importance of reporting canine infections as part of epidemiological surveillance programs to control human cases of Chagas disease.